Indonesian High School Students’ Critical Thinking and Literary Text Comprehension - Tuntun Sinaga; Budi Kadaryanto; Nurul Aulia (ELE Reviews: English Language Education Reviews, 2023)
The study aims to investigate the critical thinking and comprehension of literary texts of high school students in Bandar Lampung. The study was designed in an ex-post de facto setting with critical thinking and academic potential identified through students’ literary text comprehension. Three instruments were used in the study, i.e., an adapted reading, academic potential, and critical thinking assessment, involving tasks on summary, analysis, synthesis, and evaluation. The study reveals a noteworthy impact of explicit critical thinking training on students’ proficiency in literary text reading, alongside a significant interplay between the students’ critical thinking taxonomy and academic potential. The findings suggest the importance of a model for imparting high-order cognitive abilities, such as inferential, analytical, and synthetic skills, and active learning methods through experimentation that can be integrated into Indonesian high schools’ academic curriculums.